PENGARUH PELAPISAN STEELGUARD TERHADAP DEFORMASI PERMANEN CAMPURAN ASPAL AC-WC - Pradityo, Ardianto Tri; Vidyaning Viarsami, Vita; Nur Aisyah, Gita; Hutama Syahputra, Kevin (Direktorat Bina Teknik Jalan dan Jembatan, 2025)
Permanent deformation is a common type of distress that occurs on pavement surfaces due to the inability of the pavement structure to withstand repeated traffic loading. This type of damage leads to irreversible changes in the pavement surface, such as rutting and surface irregularities, which can compromise both driving comfort and road safety. To address this issue, innovative surface treatment solutions are needed to enhance pavement performance and service life. One such solution is SteelGuard, a polymer-modified asphalt surface coating specifically designed to repair minor surface damage. SteelGuard can be applied using spray techniques or brushed directly onto existing pavement surfaces. The research method involved two combinations of test specimens, namely asphalt concrete wearing course (AC-WC) with and without SteelGuard coating. To analyze the effect of the SteelGuard layer on permanent deformation resistance, tests were conducted using a Hamburg Wheel Tracking (HWT) under wet conditions at two temperatures, 28°C and 45°C. The analysis compared wheel passes, rut depth, Stripping Inflection Point (SIP), Number of Passes to Failure (Nf), and performance behavior during creep and stripping conditions between the two specimen combinations. The experimental results indicate that AC-WC mixtures treated with a SteelGuard coating exhibit improved resistance to permanent deformation. This improvement is evidenced by a reduction in rut depth and enhancements in other performance parameters. Based on these findings, SteelGuard is considered effective in improving the durability and functional performance of pavement surfaces, thereby contributing to longer service life and improved roadway conditions for users. Kata Kunci: Steelguard, AC-WC, deformasi permanen, hamburg wheel tracking Keywords: Steelguard, AC-WC, permanent deformation, hamburg wheel tracking